1995
DOI: 10.1007/bf00312391
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the distal pancreatic stump with a seromuscular flap

Abstract: We describe herein our new method for transecting the pancreas and closing its stump in distal pancreatectomy, devised to decrease the risk of pancreatic fistula formation. With this technique, the pancreas is transected in such a way that a convex stump is left, whereby the pancreatic secretions from the parenchyma near the pancreatic stump are fully drained into the main pancreatic duct. A pedicled seromuscular flap of the stomach or jejunum is then used to cover the cut surface of the pancreas. This new tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Numerous attempts have been described to avoid fistula formation, such as handsewn suture of the cut end, stapler closure, ligation of the main pancreatic duct 7,8 , stapler closure of the remnant using absorbable staples 9 , pancreas banding 10 , pancreaticoenteric anastomosis 11 , use of ultrasonic dissection devices 12,13 or seromuscular patches 14,15 , fibrin glue sealing 16,17 , application of surface active meshes 18 and combinations of these techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous attempts have been described to avoid fistula formation, such as handsewn suture of the cut end, stapler closure, ligation of the main pancreatic duct 7,8 , stapler closure of the remnant using absorbable staples 9 , pancreas banding 10 , pancreaticoenteric anastomosis 11 , use of ultrasonic dissection devices 12,13 or seromuscular patches 14,15 , fibrin glue sealing 16,17 , application of surface active meshes 18 and combinations of these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Following distal pancreatectomy, closure of the pancreatic remnant with a patch has been described using either an isolated Roux-n-Y loop 14 or gastric serosa 15 . A combination of the stapler technique and coverage by a seromuscular patch may provide a simple solution to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Moriura et al reported that pancreas-related complications decreased when using a seromuscular patch. 71 However, these results have not been confirmed in the randomized controlled trial by Olah et al, in which grade B/C postoperative pancreatic fistulas after stapled transection and stapled transection combined with a seromuscular patch were found to be similar. 72 In addition, the application of a falciform ligament patch and fibrin glue to standard stapled or sutured remnant closure did not reduce the rate of postoperative pancreatic fistula in patients undergoing DP.…”
Section: Glue and Patchesmentioning
confidence: 87%
“…Ultrasonic dissection devices in particular are easily available and also significantly reduce the occurrence of PF in DP [8] . Seromuscular patches [11] , fibrin glue sealing [12] , the application of surface-active meshes, and combinations of these techniques [13] were used for closure of the pancreas.…”
Section: Resection Of the Pancreas Closure Of The Remnant Pancreas mentioning
confidence: 99%
“…Seromuscular patch closure of the pancreatic remnant has been described using either an isolated Rouxn-Y loop [11] or gastric serosa [14] . Hassenpflug et al [15] reported that coverage of the pancreatic remnant after DP decreased the occurrence of clinically relevant PF.…”
Section: Resection Of the Pancreas Closure Of The Remnant Pancreas mentioning
confidence: 99%